Pengaruh Lama Perendaman dan Suhu Larutan Jeruk Nipis Terhadap Kadar Kalsium Oksalat Pada Umbi Porang - Wardani, Ratih Kusuma; Djamilah Arifiyana (Journal of Research and Technology, 2021)
Degenerative disease is a disease caused by a decrease in the condition of the human body. Degenerative diseases can be prevented with a healthy lifestyle, one of them is consuming foods with high fiber. One of the high-fiber foods that are being developed at this time is the porang tuber. Glucomannan, which is mostly contained in porang tubers, is a polysaccharide that is easily soluble in water and high in fiber. Besides containing glucomannan, porang tubers also contain lots of calcium oxalate which can cause irritation to the tongue and mouth when consuming it. Calcium oxalate levels can be lowered through immersion in acidic solution. Solution that can be used to reduce calcium oxalate levels in porang tubers is lime. Soaking time is one of the factors that affect the reduction of calcium oxalate levels. Porang tubers that have been immersed in 5% lime solution for 60 minutes showed the highest decrease, namely 31.79%. In addition, soaking at high temperatures can decrease calcium oxalate levels in porang tubers also. Porang tubers that have been immersed in a 5% lime solution at 60 ° C, the calcium oxalate level has decreased to 49.58%.